Pitfalls in Modeling Walls and Neutrals Physics in Gas Discharges Using Parallel Particle-in-Cell Monte Carlo Collision Algorithms - Gueroult, Renaud; Fubiani, Gwenael; Garrigues, Laurent (Frontiers in Physics, 2018)
Owing to their ability to model the physics of low-pressure plasmas away from thermodynamical equilibrium, particle-in-cell (PIC) techniques have become one of the tools of choice to simulate the operation of many plasma devices. This trend is reinforced by the growing access to parallel computing ressources which enables tackling problems that were previously intractable with PIC techniques. However, accurate modelling of these plasmas often depends critically on the detailed description of a variety of physical phenomena ranging from microscopic to macroscopic scale and from electrons’ to neutral particles’ timescale. Among those are coupling phenomena between charged particles and neutrals. We illustrate here how the implementation of simplified models for scattering kinematics, neutrals dynamics and particle-wall interaction can affect simulation results. Until the full breadth of these effects can be captured in models, these results underline the importance of using extensive parametric scans to assess the importance of these effects.